(untitled) (Praxis Educativa, 2026)
Considering that mathematics allows us to broaden our understanding of the world, this study evaluated the contributions of mathematical problem solving to critical education on environmental education in students in the basic cycle of four secondary schools (Entre Ríos, Argentina). The research was framed within the theoretical lines of Problem Solving and Critical Mathematics Education. Using a mixed methodology, a test with activities and a student survey were designed and implemented, complemented with semi-structured interviews with teachers. The study focused on the identification of heuristics, observing that students used different strategies. In this scenario, contextualized mathematical problem solving emerges as an innovative pedagogical alternative to create teaching and learning experiences that promote comprehensive education. The adopted perspective allowed to connect mathematics with reality, fostering the development of problem-solving skills, critical thinking and environmental responsibility.